Denis Kopylov: photography as a way of self-knowledge - Стоян, С. П. (Київський національний університет імені Тараса Шевченка, 2022)
In the article the author analyzes the photo works by Denys Kopylov who directs his gaze deep inside himself, trying to understand his own purpose in this world and focuses his attention on many current socio-cultural problems due to which his art projects are of great interest for further research in the context of cultural studies. The analysis focuses on his works devoted to the visualization of the ethno-cultural features of the Yavanava tribe, rethinking the role of the Chernobyl disaster in the context of its examination from the point of view of the revival of the animal world of the exclusion zone, recording the events of the military confrontation on the territory of Ukraine, as well as the global rethinking of the role of man on planet Earth and its relationship with the natural world. For Denys turning to photography becomes according to him a philosophy based on observation because observation is one of the basic foundations of all worldview systems. By observing ourselves we can understand our priorities and needs what we cannot live without. Through observation we can feel a kinship with specific natural forms that resonate with our inner self at this very moment in time. And thanks to this consonance the photographs begin to radiate an extremely powerful vital energy which in addition to harmonizing the author begins to harmonize the viewer as well. The study of the visualization of existing social and ecological problems in modern Ukrainian photo art is extremely relevant. In this article for the first time the photo works by artist Denys Kopylov was analyzed in the context of cultural studies with the definition of the main vectors of its direction and specificity. It is emphasized that from the reflection of his own travels and the exotic natural world, the author immerses himself in a creative study of the spirit of Indian tribes which is visualized in a modern, authentic artistic manner using innovative authorial approaches in a whole series of works that are gaining recognition both in Ukraine and abroad at prestigious world fairs.

У статті розглянута творчість фотохудожника Дениса Копилова, який спрямовує свій погляд як вглиб себе, намагаючись зрозуміти власне призначення в цьому світі, так і фокусує свою увагу на багатьох актуальних соціокультурних проблемах, завдяки чому його артпроєкти представляють значний інтерес для подальшого дослідження в контексті культурології. У здійсненому аналізі робиться акцент на його творах, присвячених візуалізації етнокультурних особливостей племені яванава, переосмисленні ролі Чорнобильської катастрофи в контексті її розгляду з точки зору відродження тваринного світу зони відчуження, фіксації подій воєнного протистояння на території України, а також глобального переосмислення ролі людини на планеті Земля та її взаємовідносин з природним світом.
Денис Копилов: фотографія як спосіб самопізнання
Keywords: фотографія; самопізнання; мистецтво; природа; Чорнобильська зона; "Ковчег «Чорнобиль»"; плем'я яванава; photography; self-discovery; art; nature; Chernobyl zone; "Chernobyl Ark"; Javanese tribe